PEMANFAATAN KECERDASAN BUATAN (AI) UNTUK MENINGKATKAN EFEKTIVITAS DAN KREATIVITAS PENULISAN ARTIKEL ILMIAH MAHASISWA - Syarif, Dafiar; Lardiman, Hendra; Patrisia, Nelly; Mu’arrif, Zul Ihsan; Sumanti, Eva; Azhar, Azhar; Harahap, Samsul Bahry; Desiana, Desiana (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to enhance students' abilities in writing scientific articles through the use of artificial intelligence (AI) technology. Based on an initial survey, the main obstacles faced by students are limited time, difficulty in understanding writing structures, and low levels of creativity in developing ideas. To address these issues, training was conducted involving the use of AI-based tools such as Grammarly, QuillBot, and ChatGPT. The activity consisted of an introductory workshop, simulations of AI usage in article writing, group discussions, and intensive mentoring. Evaluation of the program showed a significant increase in students' confidence and productivity in completing scientific articles. The publication of the scientific articles produced by the students serves as a form of appreciation and recognition of their efforts. This activity has proven effective in improving the quality of students' scientific writing and introducing the ethical use of AI technology in academia.